The Representation of Women in Saraiki Short Stories, A Feminist Critical Discourse Analysis - Saeed, Saima; Burioro, Hakim Ali (sourcecoder, 2022)
This research aims to study the Saraiki short stories of different male and female writers by using the lens of social feminism with special reference to Behavior's approach towards female identity. The analysis shows that most of writers portray women as human beings with equal rights and aspirations. Saraiki writers have portrayed most of their characters in accordance with gender stereotype that are mostly reflected in their description of appearance, domestic behavior, occupation and personality traits. Saraiki short stories depict female as a symbols respect, resistance and champions of equal rights, where they are shown to be struggling against orthodox notions of honor and gender discrimination. For a realistic portrayal, the misogyny, sexual perversion, power abuse, derogatory languages and incapacity of men have also been highlighted, mainly visible in physical appearance, in domestic behavior, in her occupation and in her personality traits. Seraiki short stories portrayed female as symbols of respect, resistance and champions of equal human rights, where they are shown to be struggling against the orthodox notions of honor and gender discrimination. For a realistic portrayal, the misogyny, sexual perversion, power abuse, derogatory language and incapacity of men have also been highlighted. Matussat Kalanchwi, Shimma siyal ,Amir Faheem, Bushra Rehmani, Habib Mohana, Hafiz Khan, are prominent writers who broke the conventional lens of patriarchy by accepting female identity as an individual ,however , their focus on objectification and body shaming of women is still not at par with the requirements of true feminist representative of today’s world, given how feminism has entered its fourth phase in the west, there is need to make the woman seen and understood as one of us ’’human’’ rather than an ‘’Other’’ who is merely there to serve and satisfy the needs of men.